Dye-based chromoendoscopy detects more neoplasia than white light endoscopy in patients with primary sclerosing cholangitis and IBD - Motta, Rodrigo V; Gupta, Vipin; Hartery, Karen; Bassett, Paul; Leedham, Simon J; Chapman, Roger W; Travis, Simon PL; Culver, Emma L; East, James E. (Endoscopy International Open, 2024)
Background and study aims Patients with primary sclerosing cholangitis and inflammatory bowel disease (IBD) have a high risk of colorectal cancer. There is no agreement on the best technique for surveillance for colorectal neoplasia. We aimed to assess whether chromoendoscopy and/or high-definition endoscopy is associated with increased detection of neoplasia in patients with primary sclerosing cholangitis undergoing surveillance compared with when they were not used.Patients and methods This was a single-center, retrospective, observational study designed to analyze differences in the detection of neoplasia (adenomatous and serrated) among patients with primary sclerosing cholangitis and IBD who underwent annual surveillance between 2010 and 2020. Multilevel logistic regression was used to adjust for confounders.Results Ninety-one patients were identified, resulting in 359 colonoscopies with 360 person-years of follow up. Over the study period, 22 of 91 patients (24%) had at least one neoplastic lesion identified; however, the mean neoplastic lesion rate was 0.87 (54/63) for the primary sclerosing cholangitis-ulcerative colitis subgroup compared with 0.24 (4/17) for the primary sclerosing cholangitis-Crohn’s disease subgroup. Chromoendoscopy was associated with a significantly higher detection rate for neoplasia (odds ratio [OR] 5.58, 95% confidence interval [CI] 2.08–14.9,P=0.001), and this association remained after adjusting for confounders, including high-definition endoscopy. High-definition endoscopes had a higher rate of neoplasia detection, but the significance was lost after adjustment for confounders, including chromoendoscopy (OR 1.93, 95% CI 0.69–5.40, P=0.21).Conclusions Chromoendoscopy is associated with a higher detection rate for neoplasia in patients with primary sclerosing cholangitis and IBD even with high-definition colonoscopes.
Keywords: Endoscopy Lower GI Tract; Inflammatory bowel disease; CRC screening; Diagnosis and imaging (inc chromoendoscopy, NBI, iSCAN, FICE, CLE...)